Kebijakan Distribusi Ekonomi Islam dalam Membangun Keadilan Ekonomi Indonesia - Ruslan Abdul Ghofur Noor (Islamica: Jurnal Studi Keislaman, 2012)
Market has always been part of development in Indonesia and in any country in that matter. How far development will succeed depends very much therefore on the nature of market. Well-managed market will certainly affect the process of development. This paper deals with the relationship between market and development with particular attention to the notion of justice. It argues that in Indonesia economic injustice is the main cause for the failure of development for many decades. The paper tries to show the many indicators of that injustice which includes among others, the unequal distribution of wealth among the citizens. The paper then moves to the economic system of Islam which ?it argues- is based on the concept of justice, and maintains that this Islamic system can be both the solution and alternative for the ailing Indonesian economy.